2012
DOI: 10.12693/aphyspola.122.444
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reversed Loading Conditions on the Mechanical Behaviour of Extruded Magnesium Alloy AZ31

Abstract: An indirectly extruded round bar of magnesium alloy AZ31 has been subjected to a cyclic test consisting of preloading in compression to dierent values of maximum stress followed by a single tensile test segment. Concurrent acoustic emission measurements were used to determine the active deformation mechanisms during plastic ow and work hardening. Electron backscattering diraction was applied to obtain local orientation images in order to reveal twins and twinned fractions of the microstructure. Twins form pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In [16], it was shown that the microstructure of AZ31 after precompression up to 150 MPa is characterized by existing of extension twins, giving a partly twinned microstructure. This is the reason why samples of both alloys, AZ31 and ZE10, were pre-compressed to 150 MPa and then subjected to tensile loading.…”
Section: Ae Response: Effect Of Pre-compression On Subsequent Tensilementioning
confidence: 99%
“…In [16], it was shown that the microstructure of AZ31 after precompression up to 150 MPa is characterized by existing of extension twins, giving a partly twinned microstructure. This is the reason why samples of both alloys, AZ31 and ZE10, were pre-compressed to 150 MPa and then subjected to tensile loading.…”
Section: Ae Response: Effect Of Pre-compression On Subsequent Tensilementioning
confidence: 99%
“…2) due to higher dislocation density which reduces the ight distance and the free length of moving dislocations. Furthermore, the detwinning process, which occurs during tensile loading, does not contribute to AE activity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Bohlen et al [17] have shown that compression-tension cyclic tests in an AZ31 magnesium alloy with various precompression stress lead to signicant changes in the AE response. In that work a preferential formation of twins occurs in large long grains that have been identied as unrecrystallized remain of the extrusion microstructure development.…”
Section: Introductionmentioning
confidence: 99%
“…For enhancing mechanical properties of Mg alloys, besides variations in alloying composition, thermomechanical treatment has a potential to be exploited. In particular, the effect of either sole heat treatment (HT), pre‐straining, or their proper combination on mechanical properties of wrought Mg alloys has attracted interest during last decades.…”
Section: Introductionmentioning
confidence: 99%
“…In extruded Mg alloys, pre‐compression along the extrusion direction (ED), that is, perpendicular to the c ‐axis of the hcp lattice structure, introduces {10‐12}<10‐11> extension twins into the microstructure . Depending on the level of the pre‐strain, various twin volume fractions can be achieved . A resulting new texture component allows the activation of deformation mechanisms (dislocation slip and twinning), which are not promoted in the initial state before pre‐straining.…”
Section: Introductionmentioning
confidence: 99%